A Community Level KAP Study on Mosquito Control in Jamnagar District - Kishor M Dhaduk; Kapil M Gandha; Bhavin N Vadera; Jitesh P Mehta; Dipesh V Parmar; Sudha B Yadav (Medsci Publications, 2013)
Background: The vectors borne diseases poses an immense public health concern and are major impediments in the path of socio-economic development. Objective: To assess domestic environment as well as community level KAP on mosquito control measures in Jamnagar district. Methods & statistics: It was a cross-sectional survey of 450 household by a pre-tested proforma analyzed by Microsoft excel office 2007. It was carried out in urban, urban slum and rural areas of Jamnagar district. Results: Rural domestic environment was favorable for mosquito breeding. Most of the respondents were unaware about the places where mosquito bred. The knowledge regarding vector, routes and symptoms of malaria was good, while majority were unaware about types of malaria and other mosquito borne diseases. Active malaria surveillance activity was totally lacking in urban area (94%), while it was very poor in rural and slum area. The preferred treatment providers in the community neither screened malaria nor imparted health education about mosquito control. 56% of the respondents were practicing at least one personal protective and larvae control measure, but less efficient one. Conclusion: Community participation in term of KAP regarding vector control is deficient at places & needs to be addressed for effective mosquito control.